Biological Responses to Nanoscale Particles Molecular and Cellular Aspects and Methodological Approaches - Gehr, Peter; Zellner, Reinhard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
In this book the recent progress accumulated in studies of the interaction of engineered nanoparticles with cells and cellular constituents is presented. The focus is on manufacturing and characterization of nanosized materials, their interactions with biological molecules such as proteins, the mechanisms of transport across biological membranes as well as their effects on biological functions. Fundamental molecular and cellular aspects are in the foreground of the book. A further particularity is the interdisciplinary approach, including fields such as preparatory and analytical chemistry, biophysics and the physics of colloids, advanced microscopy and spectroscopy for in-situ detection of nanoparticles, cellular toxicology and nanomedicine. Nanoscale particles are known to exhibit novel and unprecedented properties that make them different from their corresponding bulk materials. As our ability to control these properties is further advanced, a huge potential to create materials with novel properties and applications emerges. Although the technological and economic benefits of nanomaterials are indisputable, concerns have also been raised that nanoscale structuring of materials might also induce negative health effects. Unfortunately, such negative health effects cannot be deduced from the known toxicity of the corresponding macroscopic material. As a result, there is a major gap in the knowledge necessary for assessing their risk to human health.
Introduction -- Manufacturing methods and characterization (with respect to size, shape, surface properties, coatings, charge etc.)- Interactions of nanoparticles with proteins -- Membrane transfer mechanisms.-Cellular uptake and intracellular trafficking of nanoparticles -- Cellular responses and health effects.
Keywords: Biophysics; Nanochemistry; Cytology; Nanotechnology; Biomedical engineering; Biophysics; Nanochemistry; Cell Biology; Nanotechnology; Biomedical Engineering and Bioengineering